2001
DOI: 10.1038/sj.leu.2402222
|View full text |Cite
|
Sign up to set email alerts
|

Induction of chemoresistance in HL-60 cells concomitantly causes a resistance to apoptosis and the synthesis of P-glycoprotein

Abstract: The appearance of multidrug-resistant (MDR) proteins or the acquisition of a defective apoptotic programme are major drawbacks in the treatment of cancers since both induce a resistance to classical chemotherapy. However, a link between the two mechanisms has not, as yet, been clearly established. In this study, HL-60 cells cultured in the continual presence of a sub-lethal dose of doxorubicin (dox; HL-60/Dox) were used as a model to study acquired chemoresistance. During the induction of chemoresistance, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…16 The induction of P-glycoprotein may require higher levels of ROS generation that confer oxidative stress activate p38 MAPK and initiate the cellular antiapoptotic machinery that has been previously shown to involve P-glycoprotein. 21,42 The data of the present study show that hyperthermia increases P-glycoprotein expression in multicellular tumor spheroids by a signaling pathway that involves ROS, p38 MAPK and HIF-1␣. Hence, the beneficial role of hyperthermia in treatment of cancer patients may be counteracted by the induction of a MDR phenotype.…”
Section: Figure 11mentioning
confidence: 57%
See 1 more Smart Citation
“…16 The induction of P-glycoprotein may require higher levels of ROS generation that confer oxidative stress activate p38 MAPK and initiate the cellular antiapoptotic machinery that has been previously shown to involve P-glycoprotein. 21,42 The data of the present study show that hyperthermia increases P-glycoprotein expression in multicellular tumor spheroids by a signaling pathway that involves ROS, p38 MAPK and HIF-1␣. Hence, the beneficial role of hyperthermia in treatment of cancer patients may be counteracted by the induction of a MDR phenotype.…”
Section: Figure 11mentioning
confidence: 57%
“…16,19,20 The observed upregulation of P-glycopotein may be related to its anti-apoptotic properties, which have been previously reported and are presumably linked to P-glycoproteinmediated overexpression of the anti-apoptotic Bcl-xL protein. [21][22][23] Hyperthermia-induced upregulation of P-glycoprotein may be associated to an elevation of intracellular ROS levels. Indeed it has been recently shown that hyperthermia increases generation of ROS in HL-60 cells 24 as well as in mice, 25 and it has been suggested that hyperthermia-induced ROS may play a role as signaling molecules that transduce the stress signal to the cell nucleus.…”
mentioning
confidence: 99%
“…Among the multiple mechanisms leading to resistance to DOX (Nielsen et al, 1996), the overexpression of P-glycoprotein (P-gp), a protein that pumps out of the cell unrelated agents including DOX, is believed to account for resistance to DOX in several cell lines. It must be noted, however, that P-gp inhibition did not systematically restore DOX cytotoxicity in P-gp overexpressing cells (success (Smyth et al, 1998;Fukushima et al, 2000); failure (Campone et al, 2001)). Moreover, cells overexpressing P-gp have also been reported to resist to non-P-gp substrates such as cytosine arabinoside, staurosporine, UV irradiation, Fas receptor ligation and serum starvation (Smyth et al, 1998;Trindade et al, 1999;Campone et al, 2001).…”
Section: Introductionmentioning
confidence: 94%
“…It must be noted, however, that P-gp inhibition did not systematically restore DOX cytotoxicity in P-gp overexpressing cells (success (Smyth et al, 1998;Fukushima et al, 2000); failure (Campone et al, 2001)). Moreover, cells overexpressing P-gp have also been reported to resist to non-P-gp substrates such as cytosine arabinoside, staurosporine, UV irradiation, Fas receptor ligation and serum starvation (Smyth et al, 1998;Trindade et al, 1999;Campone et al, 2001). Taken together, these findings suggest that other mechanisms of resistance may exist in addition to P-gp overexpression.…”
Section: Introductionmentioning
confidence: 94%
“…Alterations in the apoptotic machinery have also been identified as causative determinants in melphalan resistance (2,13,14). Interactions between pro-and anti-apoptotic proteins determine cell fate in response to a host of internal and external stimuli.…”
mentioning
confidence: 99%